WAYS OF STRENGTHENING THE FINANCIAL STABILITY OF SMALL ENTERPRISES IN AZERBAIJAN (International Journal of Innovative Technologies in Economy, 2024)
Topicality. In recent years, mechanisms to support and encourage small businesses have been widely used to promote the positive impact of income distribution on the development of a competitive economy, poverty reduction and rapid response to changing market conditions.Aim and tasks. The primary aim of this research is to investigate and enhance the financial stability of small enterprises in Azerbaijan, emphasizing their crucial role in the country's economic development. The research evaluates the profitability and management efficiency of small enterprises through indicators such as general profitability, net profitability, net return on equity, and total profitability of production funds.Materials and methods. Data Collection, literature review, mathematical analysis methods were used in the study. There are methods of financial planning aimed at studying its object, and the preparation of this financial plan is carried out by various methods. Among them, we can show methods on the coefficient, methods on the norm, and also methods on the balance. As a result of determining financial ratios, financial risks can be analyzed and eliminated. To achieve stability, it is necessary to analyze financial ratios, which are relative indicators of the financial condition of the enterprise. These coefficients are calculated as the ratio of absolute indicators or their complex. The analysis of financial ratios is carried out by comparing their values for periods (report and base).Research results. While each enterprise demonstrates its unique financial performance, "Karmen LLC" appears to exhibit promising signs of stability with positive profitability, reasonable liquidity, and efficient management. However, continuous monitoring and strategic planning are necessary for sustaining and enhancing their financial health and market stability.Conclusion. The financial analysis of "Karmen LLC", "Azdad 2020 LLC", "Karvan L LLC", and "NEON LLC" highlights variations in their financial stability, profitability, and management efficiency. While "Karmen LLC" and "Azdad 2020 LLC" demonstrate stronger financial positions and profitability, "Karvan L LLC" and "NEON LLC" face challenges such as lower liquidity and profitability. Further research should focus on industry benchmarking, trend analysis, and qualitative assessments to provide a more comprehensive understanding of their financial performance and prospects. These insights will be crucial for informed decision-making and strategic planning in the competitive business landscape.